1997
DOI: 10.1159/000179213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Intensity Endurance Training on the Capillary Network in Rat Skeletal Muscle

Abstract: Effects of low- and high-intensity endurance training on the capillary luminal diameter and number were studied morphometrically in the rat plantaris muscle. Male Wistar-Imamichi rats were divided into three groups: sedentary control group (Cont, n = 9), low-intensity (running speed of 20 m/min) training group (T-20, n = 8) and high-intensity (running speed of 40 m/min) training group (T-40, n = 7). Rats in both training groups were subjected to each treadmill running program for 60 min/day, 5 days/week for 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Since the increases in the cross‐sectional area (CSA) of the abdominal inferior vena cava (Miyachi, Okutsu, Nakahara, and Saitoh, ) and femoral vein (Miyachi et al, ) were observed after endurance training for 8–12 weeks, venous expansion is likely to be caused by not only I‐TRA but also C‐TRA. In contrast, an animal study revealed that continuous endurance training for 9 weeks induced not only increased capillary numbers but also increased capillary luminal diameter, and this adaptive response of capillary diameter to endurance training was dependent on training intensity (Kano et al, ). In the present study, because calf volume measured by venous occlusion plethysmography reflects the vascular responses of all arteries, veins, and capillaries in the whole limb, we cannot exclude the possibility that the increased capillary volume due to changes in number and/or diameter after both interval and continuous training for 8 weeks could result in increased calf volume and venous capacitance in both I‐TRA and C‐TRA.…”
Section: Discussionmentioning
confidence: 99%
“…Since the increases in the cross‐sectional area (CSA) of the abdominal inferior vena cava (Miyachi, Okutsu, Nakahara, and Saitoh, ) and femoral vein (Miyachi et al, ) were observed after endurance training for 8–12 weeks, venous expansion is likely to be caused by not only I‐TRA but also C‐TRA. In contrast, an animal study revealed that continuous endurance training for 9 weeks induced not only increased capillary numbers but also increased capillary luminal diameter, and this adaptive response of capillary diameter to endurance training was dependent on training intensity (Kano et al, ). In the present study, because calf volume measured by venous occlusion plethysmography reflects the vascular responses of all arteries, veins, and capillaries in the whole limb, we cannot exclude the possibility that the increased capillary volume due to changes in number and/or diameter after both interval and continuous training for 8 weeks could result in increased calf volume and venous capacitance in both I‐TRA and C‐TRA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the higher end of exercise intensities, Cocks et al reported that repeated all-out 30 s Wingate bouts lead to an increase in capillarization (66). Accordingly, in rodents, high intensity exercise has been shown to be similarly effective in inducing capillarization (155,222). Thus, based on existing data it seems reasonable to conclude that high intensity training has a similar effect on capillary growth as more moderate intensity exercise in sedentary individuals.…”
Section: High-intensity Intermittent Trainingmentioning
confidence: 99%
“…As described previously (36), locations of muscle fibers and capillaries in skeletal muscle cross sections were obtained from photomicrographs of rat plantaris (26) and rat extensor digitorum longus (EDL) (F. HansenSmith, personal communication). The images were scanned, digitized, and subdivided into pixels, representing 2 ϫ 2-m regions of tissue, each of which was designated as capillary, muscle fiber, or interstitial space.…”
Section: Configurations Of Muscle Fibers and Capillariesmentioning
confidence: 99%